Isolation of new probes from Xq12-->q13: an example of the screening of reference libraries with Alu-PCR products from radiation hybrids. - Muscatelli, F; Monaco, A; Goodfellow, P; Hors-Cayla, M; Lehrach, H; Fontes, M (1992)
In order to isolate new probes from the juxtacentromeric region of the long arm of the human X chromosome, we used Alu-mediated polymerase chain reaction (Alu-PCR) products as probes to directly screen a chromosome X-specific gridded cosmid library. These Alu-PCR products were synthesized from radiation hybrids containing the loci DXS159, PGK1, and PGK1P1. This approach allowed us to select 18 cosmids capable of hybridizing with at least two Alu-PCR products. Four cosmids hybridized to more than three Alu-PCR products. Three of these four cosmids were contiguous, and the fourth was independent. Two cosmids that hybridized with two Alu-PCR products were further characterized. Physical mapping indicated that all of these clones are located in the expected region on Xq, confirming the validity of our approach.